(untitled) (Asian Business Research, 2022)
With the development of the new generation of Internet technology, digital economy plays an important role in the economic society. Under the new social development trend, how to deal with the antitrust supervision problems brought by the large-scale Internet platform has become a common challenge faced by governments all over the world. China’s digital economy antitrust has entered a period of comprehensive supervision. Therefore, we need to fully understand the causes of platform economic monopoly, put forward a more perfect and scientific scheme for the supervision of platform antitrust, and pave the way for the sustainable and healthy development of platform economy.